(a2+b2) (x2+y2)=(ax+by)2
<=>a2x2+a2y2+b2x2+b2y2=a2x2+2axby+b2y2
<=>a2x2+a2y2+b2x2+b2y2-a2x2-2axby-b2y2=0
<=>a2y2+b2x2-2aybx=0
<=>(ay-bx)2=0
<=>ay-bx=0
<=>ay=bx
=>a/x=b/y
(a2+b2) (x2+y2)=(ax+by)2
<=>a2x2+a2y2+b2x2+b2y2=a2x2+2axby+b2y2
<=>a2x2+a2y2+b2x2+b2y2-a2x2-2axby-b2y2=0
<=>a2y2+b2x2-2aybx=0
<=>(ay-bx)2=0
<=>ay-bx=0
<=>ay=bx
=>a/x=b/y
Cho ax + by + cz = 0. CMR:
ax^2 + by^2 + cz^2/ bc(y-z)^2 + ca(z-x)^2 + ab(x-y)^2 = 1/a+b+c
1.cho x,y thỏa mãn: ax+by=c,bx+cy=a,cx+by=b
CMR:a^3+b^3+c^3=3abc.
2.cho a,b,c khác 0 sao cho:ay-bx/c=cx-az/b=bz-cy/a
CMR:(ax+by+cz)=(x^2+y^2+z^2)(a^2+b^2+c^2)
cho các số a, b, x, y # 0. CMR : (ax+by)^2 < (a^2+b^2)(x^2+y^2) -- dấu bằng xảy ra khi nào
Cho a,b,c,x,y,z là các số dương thỏa mãn (a^2+b^2+c^2) (x^2+y^2+z^2) = (ax + by + cz)^2
CMR a/x = b/y + c/z
Cho a,b,c,x,y,z là các số dương thỏa mãn (a^2+b^2+c^2) (x^2+y^2+z^2) = (ax + by + cz)^2
CMR a/x = b/y + c/z
CMR nếu x/a=y/b=z/c thì (x^2+y^2+z^2)(a^2+b^2+c^2)=(ax+by+cz)^2
biết x = a^2 - bc , y^2 = b^2 - ac , z = c^2 - ab . Cmr : ( x+y+z)(a+b+c)=ax+by+cz
biết x = a^2 - bc , y^2 = b^2 - ac , z = c^2 - ab . Cmr : ( x+y+z)(a+b+c)=ax+by+cz
1 Cho a+b+c =0; a^2+b^2+c^2 =1.CMR a^4+b^4+c^4=1/2
2Cho a^2-b^2=4c^2 CMR (5a-3b+8c)(5a-3b-8c)=(3a-5b)^2
3 CMR Nếu (a^2+b^2)(x^2+y^2)=(ax+by)^2 với x,y khác o thì a/x=b/y